Pythagorean Generator Matrix

( x y y y x y y y z ) ( a b c ) = ( a b c ) \begin{pmatrix}x & y & y \\ y & x & y \\ y & y & z \end{pmatrix}\begin{pmatrix}a \\ b \\ c \end{pmatrix} = \begin{pmatrix}a' \\ b' \\ c' \end{pmatrix} If the above equation holds true, then there exist coprime positive integers x , y , z x, y, z such that any Pythagorean triple ( a , b , c ) (a, b, c) produces another Pythagorean triple ( a , b , c ) . \big(a', b', c'\big).

Find the sum of such x , y , x, y, and z . z.


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Mar 13, 2018

Using matrix multiplication, we have a = a x + b y + c y a' = ax + by + cy , b = a y + b x + c y b' = ay + bx + cy , and c = a y + b y + c z c' = ay + by + cz . As Pythagorean triples, a 2 + b 2 = c 2 a^2 + b^2 = c^2 and a 2 + b 2 = c 2 a'^2 + b'^2 = c'^2 . Therefore, ( a x + b y + c y ) 2 + ( a y + b x + c y ) 2 = ( a y + b y + c z ) 2 (ax + by + cy)^2 + (ay + bx + cy)^2 = (ay + by + cz)^2 , which simplifies to ( x 2 + 2 y 2 z 2 ) c 2 (x^2 + 2y^2 - z^2)c^2 + + 2 ( x y + x y y 2 ) a b 2(xy + xy - y^2)ab + + 2 ( x y + y 2 y z ) a c 2(xy + y^2 - yz)ac + + 2 ( y 2 + x y y z ) b c 2(y^2 + xy - yz)bc = = 0 0 , which is true if x 2 + 2 y 2 z 2 = 0 x^2 + 2y^2 - z^2 = 0 , 2 x y y 2 = 0 2xy - y^2 = 0 , and x y + y 2 y z = 0 xy + y^2 - yz = 0 .

From 2 x y y 2 = 0 2xy - y^2 = 0 we have y ( 2 x y ) = 0 y(2x - y) = 0 , and since y y is a positive integer, y = 2 x y = 2x .

From x y + y 2 y z = 0 xy + y^2 - yz = 0 we have y ( x + y z ) = 0 y(x + y - z) = 0 , and since y is a positive integer, z = x + y z = x + y , and since y = 2 x y = 2x , z = 3 x z = 3x .

Since y = 2 x y = 2x and z = 3 x z = 3x , x 2 + 2 y 2 z 2 = x 2 + 2 ( 2 x ) 2 ( 3 x ) 2 = 0 x^2 + 2y^2 - z^2 = x^2 + 2(2x)^2 - (3x)^2 = 0 .

So ( x , y , z ) = ( x , 2 x , 3 x ) (x, y, z) = (x, 2x, 3x) , and for x x , y y , and z z to be coprime we must have x = 1 x = 1 , y = 2 y = 2 , and z = 3 z = 3 , and 1 + 2 + 3 = 6 1 + 2 + 3 = \boxed{6} .


Alternatively, let a 2 + b 2 = c 2 a^2 + b^2 = c^2 . Then ( n a ) 2 + ( n b ) 2 = ( n + c ) 2 (n - a)^2 + (n - b)^2 = (n + c)^2 for n = 0 n = 0 and, as a quadratic, possibly a second value of n n . Solving this equation for the other value gives n = 2 a + 2 b + 2 c n = 2a + 2b + 2c . Therefore, a = n a = a + 2 b + 2 c a' = n - a = a + 2b + 2c b = n b = 2 a + b + 2 c b' = n - b = 2a + b + 2c c = n + c = 2 a + 2 b + 3 c c' = n + c = 2a + 2b + 3c (We also note that a 2 + b 2 = c 2 a'^2 + b'^2 = c'^2 , so it is not an extraneous solution.) This means ( 1 2 2 2 1 2 2 2 3 ) ( a b c ) = ( a b c ) \begin{pmatrix}1 & 2 & 2 \\ 2 & 1 & 2 \\ 2 & 2 & 3 \end{pmatrix}\begin{pmatrix}a \\ b \\ c \end{pmatrix} = \begin{pmatrix}a' \\ b' \\ c' \end{pmatrix} Therefore, x = 1 x = 1 , y = 2 y = 2 , and z = 3 z = 3 , and 1 + 2 + 3 = 6 1 + 2 + 3 = \boxed{6} .


This and some other Pythagorean Generator Matrices can be found here .

Beautiful question and a beautiful solution!

Ramasamy Pullappan - 3 years, 2 months ago
Arjen Vreugdenhil
Mar 25, 2018

Since David gave us matrix notation, we'll solve using matrix techniques!

( a , b , c ) (a,b,c) is a Pythagorean triple iff a 2 + b 2 c 2 = 0 a^2 + b^2 - c^2 = 0 , or ( a b c ) ( 1 1 1 ) ( a b c ) = 0. \begin{pmatrix} a & b & c \end{pmatrix} \begin{pmatrix} 1 & & \\ & 1 & \\ & & -1 \end{pmatrix} \begin{pmatrix} a \\ b \\ c \end{pmatrix} = 0. Likewise, for ( a , b , c ) (a',b',c') to be a Pythagorean triple we must have ( a b c ) ( x y y y x y y y z ) ( 1 1 1 ) ( x y y y x y y y z ) ( a b c ) = 0. \begin{pmatrix} a & b & c \end{pmatrix} \begin{pmatrix} x & y & y \\ y & x & y \\ y & y & z \end{pmatrix} \begin{pmatrix} 1 & & \\ & 1 & \\ & & -1 \end{pmatrix} \begin{pmatrix} x & y & y \\ y & x & y \\ y & y & z \end{pmatrix} \begin{pmatrix} a \\ b \\ c \end{pmatrix} = 0. The former equation must imply the latter for a large number of linearly independent Pythagorean triples ( a , b , c ) (a,b,c) . This is only possible if the following matrix equation holds: ( x y y y x y y y z ) ( 1 1 1 ) ( x y y y x y y y z ) = ( 1 1 1 ) N , \begin{pmatrix} x & y & y \\ y & x & y \\ y & y & z \end{pmatrix} \begin{pmatrix} 1 & & \\ & 1 & \\ & & -1 \end{pmatrix} \begin{pmatrix} x & y & y \\ y & x & y \\ y & y & z \end{pmatrix} = \begin{pmatrix} 1 & & \\ & 1 & \\ & & -1 \end{pmatrix} N, for a constant N N . We will start taking N = 1 N = 1 , and afterward multiply by any common denominator or divide by any common factor if necessary.

Performing the matrix multiplication, we find four independent equations: { x 2 = 1 ( 2 x y ) y = 0 ( x + y z ) y = 0 2 y 2 z 2 = 1 \begin{cases} x^2 = 1 \\ (2x-y)y = 0 \\ (x+y-z)y = 0 \\ 2y^2-z^2 = -1 \end{cases} Working with positive numbers only, we derive from the first three equations x = 1 ; y = 2 ; z = 3 , \boxed{x = 1;\ \ y = 2;\ \ z = 3}, and the fourth equation checks out (remarkably!): 2 2 2 3 2 = 1 2\cdot 2^2 - 3^2 = -1 .

Since these three values are integer and coprime, there is no need to adjust the constant N N . Thus the answer to the problem is 1 + 2 + 3 = 6 1 + 2 + 3 = \boxed{6} .

Great solution!

David Vreken - 3 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...